Hüseyin Rahmi Gürpınar’ ın romanlarında çocuk - Tilki, Bahriye (My University, 1991)
unknown
Keywords: 1800 - 1849; 19. yüzyıl; Edebiyat; EDEBİYAT-ROMAN-TÜRK; GÜRPINAR, HÜSEYİN RAHMİ, 1864-1944; Türkçe roman ve hikaye